A Research Study on Guidance from The Teachings and Life Practices of Prophet Muhammad (PBUH) to Cure from Corona and other Pandemics - Shah, Syed Muhammad Tahir; Alam, Syed Aftab (Journal of Islamic and Religious Studies, 2021)
Human history has faced numberless pandemics; however, the contemporary pandemic Covid-19 proved the most fatal and dangerous amongst all. Although vaccines have been prepared, launched, and injected in almost all around the world but according to the medical experts, human life seems to be vulnerable to its new expected waves and novel variants. The only suggested solution is advised to follow its SOPs. Public must change their lifestyle and behaviors forever according to these SOPs for survival of humanity. The basic question of this research is whether we found any role model, instructions, or example from The Prophet (S.A.W). The paper elaborates the aspects of Sīrat-un-Nabi (S.A.W) in this regard. He (S.A.W) indicated the reasons of pandemics, their remedies, and their spiritual and practical solutions. He (S.A.W.) not only stated the status of the victims and expired individuals due to the pandemics but also taught the humanity more than the SOPs recommended by medical experts for saving lives from corona infection. Humanity can be saved from the pandemics and losses can be reduced by acting upon and following the precautionary measures and SOPs recommended by the Prophet (S.A.W), like the social distancing, lockdown, covering the mouth (mask), quarantine, avoiding the hand shaking and hugging with the patients and the strict instructions of regular cleanliness.